Manejo presupuestario y su incidencia en la información financiera de la universidad técnica de Cotopaxi en los periodos económicos 2014 – 2017. - Arizaga Muñoz, Julia Elena (2018)
The budgetary institutional programming will be sustained in the multiannual plan for a horizon of four years that every institution will elaborate in consistency with the multiannual plan of the government for the same period and in the operative annual plans that are formulated for his concretion. The operative annual plans will constitute the link that will allow to link the aims and goals of the multiannual plans with the goals and results of the programs incorporated in the budget. For such an effect, the aims and goals of the multiannual plan will express in operative aims and goals of the annual plans, of which there will be defined the set of necessary actions and the requirements of human, material, physical and financial resources for his attainment.